Executive functions as predictors of critical thinking: Behavioral and neural evidence. (February 2021) - Li, Shuangshuang; Ren, Xuezhu; Schweizer, Karl; Brinthaupt, Thomas M.; Wang, Tengfei
Abstract: Theories of critical thinking suggest that executive functions play crucial roles in students' critical thinking performance. However, very little empirical research has examined the potential confounding factors of fluid intelligence and thinking dispositions on the relationship between executive functions and critical thinking. Study 1, based on a large sample of university students, filled this gap by exploring how three core executive functions (updating, inhibition, and shifting) predicted critical thinking after controlling for fluid intelligence and thinking dispositions. The results showed that updating and inhibition predicted critical thinking over and above fluid intelligence and thinking dispositions. In Study 2, we explored the neural basis of the relationship between executive functions and critical thinking. We found that low-level critical thinkers exhibited higher P3 amplitudes than their high-level counterparts when completing updating and inhibition tasks. These results suggest that critical thinking relies on both updating and inhibition processes indexed by the P3 ERP components. Highlights: The unique role of three core executive functions in critical thinking was examined. The electrophysiological nature of critical thinking was explored by ERP techniques. Updating predicted critical thinking beyond intelligence and thinking dispositions. Inhibition predicted critical thinking beyond intelligence and thinking dispositions. Low-level critical thinkers exhibited higher P3 amplitudes than high-level thinkers.